ANALISIS FAKTOR KERUSAKAN LINGKUNGAN TERHADAP LAHAN DI SEKITAR PABRIK BATU BATA DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Sulistia Budi; Zulfan Saam; Sukendi Sukendi (Program Pascasarjana Universitas Riau, 2015)
Growth of the brick industry in the city of Pekanbaru is growing rapidly along with thedevelopment in all sectors of development . The presence of the brick industry has apositive impact on the economic development of the communities around the industry.However, the presence of the brick industry has contributed to changes physical andbiological environment. This study aims to analyze the physical and biological qualityin the area of former clay mining , as well as to determine the level of damage to theenvironment. The research was carried out at RT 01 RW 22 Sub Sub Tenayan SailPekanbaru Riau Kingdom. The research method is a survey method by asking somequestions to the respondents, but it was also an indicator measuring physical damagedirectly at the study site (In situ). The data were analyzed descriptively in the form ofsentences, tables and photographs. Associated measurement results obtained withEnviromental Decree No. 43 of 1996 concerning the business or environmental damagecriteria mining quarrying category C echo off the mainland. Data obtained from thesurvey results as follows. Conditions tofografi pit depth at station 1 (1.2 m), 2 (1.68 m),3 (0.9 m), 4 (1.75 m), station 1.2, and 4 categorized suffered damage, 3 stations are notdamaged. Distance between pits stations 1(1.26 m, 2 (7.01 m), 3 (3.06 m), 4 (7m).Differences in basic relief excavated at stations 1(1.79 m ), 2 (1.83 m), 3 (0.96 m), 4(1.48 m), station 1, 2 and 4 were damaged . The slope of the excavation at station 1(9.60 % ), 2 (15.47 % ), 3 (20.41 %), 4 (31.84 %) , four stations have been damaged.Cliff terrace excavation wall at station 1 (1.44 m), 2 (1.83 m), 3 (1.31 m), 4 (3.03 m).Stations categorized 1,2,3 not damaged, while station 4 categorized damaged. basiswall terrace excavation at station 1 (2,56 m) , 2 (1,61 m), 3 (1,01 m), 4 (1,38 m), whichobserved the four stations were damaged. fourth station that observed there is no landis returned as a cover, thus resulting in the absence of vegetation encountered around the mined lands. Based on the measurements it can be concluded that the physical andbiological conditions in the area of former clay mines suffered moderate damage.